The Paris Agreement objectives will likely halt future declines of emperor penguins. (7th November 2019) - Jenouvrier, Stéphanie; Holland, Marika; Iles, David; Labrousse, Sara; Landrum, Laura; Garnier, Jimmy; Caswell, Hal; Weimerskirch, Henri; LaRue, Michelle; Ji, Rubao; Barbraud, Christophe
Abstract: The Paris Agreement is a multinational initiative to combat climate change by keeping a global temperature increase in this century to 2°C above preindustrial levels while pursuing efforts to limit the increase to 1.5°C. Until recently, ensembles of coupled climate simulations producing temporal dynamics of climate en route to stable global mean temperature at 1.5 and 2°C above preindustrial levels were not available. Hence, the few studies that have assessed the ecological impact of the Paris Agreement used ad‐hoc approaches. The development of new specific mitigation climate simulations now provides an unprecedented opportunity to inform ecological impact assessments. Here we project the dynamics of all known emperor penguin ( Aptenodytes forsteri ) colonies under new climate change scenarios meeting the Paris Agreement objectives using a climate‐dependent‐metapopulation model. Our model includes various dispersal behaviors so that penguins could modulate climate effects through movement and habitat selection. Under business‐as‐usual greenhouse gas emissions, we show that 80% of the colonies are projected to be quasiextinct by 2100, thus the total abundance of emperor penguins is projected to decline by at least 81% relative to its initial size, regardless of dispersal abilities. In contrast, if the Paris Agreement objectives are met, viable emperor penguin refuges will exist in Antarctica, and only 19% and 31% colonies are projected to be quasiextinct by 2100 under the Paris 1.5 and 2 climate scenarios respectively. As a result, the global population is projected to decline by at least by 31% under Paris 1.5 and 44% under Paris 2. However, population growth rates stabilize in 2060 such that the global population will be only declining at 0.07% under Paris 1.5 and 0.34% under Paris 2, thereby halting the global population decline. Hence, global climate policy has a larger capacity to safeguard the future of emperor penguins than their intrinsic dispersal abilities. Abstract : Using newly developed mitigation ensembles of fully coupled climate simulations consistent with meeting the Paris Agreement objectives, we derive robust projections of future population dynamics and species persistence for the emperor penguin. We show that global climate policy has the capacity to halt the future projected declines of emperor penguins in ways that their intrinsic biological properties (i.e., dispersal abilities) do not.